The Business Plan for Productive Waqf: Synergy between Asset Management and Risk Management - Uti Himayah (ICO EDUSHA, 2024)
Productive waqf is one strategy to optimize waqf assets so that they have sustainable benefits for the community. A productive waqf business plan needs to be prepared by considering efficient asset management and effective risk management. This article aims to examine the synergy between asset management and risk management in the implementation of productive waqf, so that it can increase the value of waqf assets and maintain their sustainability. The research method used is a qualitative approach with literature analysis and case studies on productive waqf management institutions in Indonesia. The results of the study indicate that effective asset management and systematic risk management can optimize the benefits of productive waqf and minimize potential risks that can hinder its sustainability. Keywords : Productive waqf, asset management, risk management, business plan, sustainability.